Ji-Ni-De-Xie ameliorates type 2 diabetes mellitus by modulating the bile acids metabolism and FXR/FGF15 signaling pathway - Tao, Yiwen; Peng, Fang; Wang, Lijie; Sun, Jiayi; Ding, Yin; Xiong, Shuangfeng; Tenzin, Ugen; MiMa,; Nhamdriel, Tsedien; Fan, Gang (Frontiers in Pharmacology, 2024)
Ji-Ni-De-Xie (JNDX) is a traditional herbal preparation in China. It is widely used to treat type 2 diabetes mellitus (T2DM) in traditional Tibetan medicine system. However, its antidiabetic mechanisms have not been elucidated. The aim of this study is to elucidate the underlying mechanism of JNDX on bile acids (BAs) metabolism and FXR/FGF15 signaling pathway in T2DM rats. A total of 12 constituents were identified by high-performance liquid chromatography-triple quadrupole mass spectrometry (HPLC-QQQ-MS) in JNDX. Furthermore, 45 chemical components in serum were identified from JNDX via UPLC-Q-Exactive Orbitrap MS technology, including 22 prototype components and 23 metabolites. Using a T2DM rat model induced by high-fat diet (HFD) and streptozotocin (45 mg∙kg-1) (STZ), we found that JNDX (0.083, 0.165 and 0.33 g/kg) reduced the levels of fasting blood glucose (FBG), glycosylated serum protein (GSP), homeostasis model assessment of insulin resistance (HOMA-IR), LPS, TNF-α, IL-1β, IL-6, TG, TC, and LDL-C, and increased insulin sensitivity index (ISI) and HDL-C levels in T2DM rats. Metagenomic results demonstrated that JNDX treatment effectively improved gut microbiota dysbiosis, including altering some bacteria (e.g., Streptococcus and Bacteroides) associated with BAs metabolism. Additionally, JNDX improved BAs disorder in T2DM rats, especially significantly increasing cholic acid (CA) levels and decreasing ursodeoxycholic acid (UDCA) levels. Moreover, the protein and mRNA expressions of FXR and FGF15 of T2DM rats were significantly increased, while the expression of CYP7A1 protein in the liver was markedly inhibited by JNDX. In conclusion, JNDX can effectively improve insulin resistance, hyperglycemia, hyperlipidemia, and inflammation in T2DM rats. The mechanism is related to its regulation of BAs metabolism and activation of FXR/FGF15 signaling pathway.